Myasthenia Gravis With Antibodies Against Muscle Specific Kinase: An Update on Clinical Features, Pathophysiology and Treatment - Cao, Michelangelo; Koneczny, Inga; Vincent, Angela (Frontiers in Molecular Neuroscience, 2020)
Muscle Specific Kinase myasthenia gravis (MuSK-MG) is an autoimmune disease that impairs neuromuscular transmission leading to generalized muscle weakness. Compared to the more common myasthenia gravis with antibodies against the acetylcholine receptor (AChR), MuSK-MG affects mainly the bulbar and respiratory muscles, with more frequent and severe myasthenic crises. Treatments are usually less effective with the need for prolonged, high doses of steroids and other immunosuppressants to control symptoms. Under physiological condition, MuSK regulates a phosphorylation cascade which is fundamental for the development and maintenance of post-synaptic AChR clusters at the neuromuscular junction (NMJ). Agrin, secreted by the motor nerve terminal into the synaptic cleft, binds to LRP4 which activates MuSK. In MuSK-MG, monovalent MuSK-IgG4 autoantibodies block MuSK-LRP4 interaction preventing MuSK activation and leading to the dispersal of AChR clusters. Lower levels of divalent MuSK IgG1, 2 and 3 antibody subclasses are also present but their contribution to the pathogenesis of the disease remains controversial. The aim of this review is to provide a detailed update on the epidemiological and clinical features of MuSK-MG, focusing on the pathophysiological mechanisms and the latest indications regarding efficacy and safety of different treatment options.